Thiamine use is associated with better outcomes for traumatic brain injury patients - Wang, Ruoran; Zeng, Yunhui; Xu, Jianguo; He, Min (Frontiers in Nutrition, 2024)
Background: Traumatic brain injury (TBI) is a worldwide health issue leading to poor prognosis. We design this study to explore whether thiamine use is associated with a better prognosis of TBI.: TBI patients collected from the Medical Information Mart for Intensive Care-III were included. Univariate and multivariate Cox regression were performed to analyze the relationship between thiamine use and mortality of TBI. Propensity score match (PSM) was utilized to generate balanced cohorts of the non-thiamine use group and thiamine use group. Sub-group analysis was performed to verify the association between thiamine use and mortality of TBI in different stratifications after PSM.The thiamine use incidence in TBI was 18.3%. The thiamine use group had lower 30-day mortality (p<0.001), longer length of ICU stay (p<0.001), and length of hospital stay (p<0.001) than the non-thiamine use group both in the primary cohort before PSM and the cohort after PSM. Multivariate Cox regression confirmed that thiamine use was independently associated with mortality (OR=0.454, p<0.001) after adjusting confounding effects. In the cohort after PSM, sub-group analysis showed that thiamine use is associated with lower mortality of TBI patients with Glasgow Coma Scale (GCS) <13 but not associated with mortality of TBI patients whose GCS ≥13.Thiamine supplementation is effective in improving the outcome of TBI except for mild TBI. The optimal thiamine supplementation strategy for TBI is worthwhile to be explored in future studies.